Development of Media Fun Thinkers Book Material for The Diversity of Living Things for Class IV Elementary School - Nur Anggraini, Pipin; Asmarani, Ratih (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
In the implementation of learning activities that occur at SD Plus Pesantren Al-Anwar, problems when implementing learning activities, among others, are the media used are not supportive, teachers use learning resources in the form of books and have not used certain learning media. This is the cause of students tend to be passive in learning activities. When learning theme 3 sub-theme 2 learning 2 in class IV the teacher uses image media in teaching and learning activities, making students less understanding of the material. As a result, students are less interested in teaching and learning activities. This research was conducted in class IV, which consisted of 20 students. In the development research that has been carried out, it is expected to be able to provide a good influence for students, the Fun Thinkers book media is to foster student learning activities and achievements and must use media that can foster student interest in learning so that they are enthusiastic in undergoing the learning process. Research using the ADDIE model which passes through 5 stages.